南極成層圏におけるオゾン破壊とPSC・大気微量成分の継続的観測の重要性 - 武田, 真憲; 佐伯, 浩介; 木, 名瀬健; 長浜, 芳寛; Michael, C. Pitts; 中島, 英彰; Masanori, Takeda; Kosuke, Saeki; Takeshi, Kinase; Yoshihiro, Nagahama; Hideaki, Nakajima (2013)
The magnitude of ozone hole in winter polar stratosphere is related to the occurrence frequency of polar stratospheric clouds (PSCs). The threshold temperature for PSC formation depends on the amount of stratospheric nitric acid and water vapor. Recently, a long-term positive and negative trend in stratospheric water vapor was reported (Solomon et al. 2010). To understand ozone destruction mechanism in polar region, it is necessary to continuously observe stratospheric trace gases which are related to ozone chemistry, and resolve PSC’s formation process and their composition. The observation techniques for stratospheric trace gases and PSCs include observation by using Fourier transform infrared spectroscopy (FTIR), balloonborne sondes and satellites. To date, we have been analyzed these observational data for more than 6 years since 2007. We report some results and further introduce the future observation plan in Syowa Station. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 国立極地研究所 ３階ラウンジ conference object